Primal intelligence : you are smarter than you know - Fletcher, Angus (Avery, an imprint of Penguin Random House, 2025)
"Tap into your hidden intelligence and transform your life The creative spark of Vincent van Gogh. The business acumen of Steve Jobs. The mental resilience of Maya Angelou. The transformative leadership of Abraham Lincoln. The communication knack of William Shakespeare. In 2021, researchers at Ohio State's Project Narrative, renowned for collaborations with NASA, Hollywood, and Silicon Valley, announced that they had discovered the neural power at the root of all this human genius. They named it Primal Intelligence. Intrigued, US Army Special Operations developed Primal Intelligence training for its most classified units. The training succeeded. The Operators saw the future faster. They healed quicker from trauma. In life-and-death situations, they chose wiser. The Army then ran trials on military nurses, pilots, engineers, and commanders-and on civilian entrepreneurs, doctors, managers, salespeople, teachers, investors, and NFL players. Their leadership and innovation improved significantly. They coped better with change and uncertainty. They experienced less anxiety and anger. Finally, the Army authorized trials on college and K-12 students. The training produced substantial effects in students as young as eight. In 2023, the Army awarded Project Narrative a medal for "groundbreaking research." The revolutionary training that US Army Special Operations and Project Narrative created is now available for the first time in this book. The training is simple, not easy. It's not an optimization hack or a cheat code. It's a different way of using your brain. It offers a new neuroscientific approach to intuition, imagination, emotion, and commonsense, helping you become more like van Gogh and Jobs, Lincoln and Angelou. It gives you the tools to unlock the ancient know-how you forgot you knew. Your human genius. Your Primal Intelligence"--